Closing address - Watson, Jim (New Zealand Science Review, 2010)
It is my great pleasure to close this most stimulating day with some comments. I appreciate that in this room we have together the key people who can make a real difference to the food industry in New Zealand. I would especially like to acknowledge the presence of Dr Dijkhuizen and the contingent from Wageningen University, and Hans Ramaker from the New Zealand Embassy of the Kingdom of the Netherlands, and the Members of Parliament here. Together you have created a most memorable day.We have heard from seven speakers, each providing a different perspective in terms of our research capability and our educational facilities to fully exploit our potential in agri-food.We must make the transformational changes that are needed to ensure we do.